Antidepressants and, suicide and self-injury: Causal or casual association?. (2nd January 2016) - Pozzi, Marco; Radice, Sonia; Clementi, Emilio; Molteni, Massimo; Nobile, Maria
ABSTRACT: Objective : The causal relationship between antidepressants and the increase of self-injury and suicide in the paediatric age is highly debated. The black-box warnings about increased risks of suicidal thinking and behaviour in children and young adults, led to a reduction in both treatment and diagnosis of depression also in adults, in the face of an increasing need for therapies. The debate originates also from contrasting reports in the literature. Methods : We carried out an interpretative review of the most recent reports (2012–2014), from which three topics emerged. Results : First, the presence of populations with different baseline risks of self-injury among published works introduced bias in the results. Second, the application of inappropriate or excessively variegated outcome measures for self-injury introduced confounding factors that prevent the successful conduction of meta-analyses. This hinders constructive debate involving different groups, as shown in the correspondence by senior authors in the field. Third, the regulatory actions that limited the prescription of antidepressants were taken in perspective of scientific advances, not yet due. This turned temporary cautions into long-lasting limitations. Conclusions : While some clinical improvements can already be suggested, only the fulfilment of this debate will allow to revise the black-box warnings and to improve the antidepressant therapies.